Balustrade around inner dome - Ghosh, Ayan (2023)
Though artificially illuminated now, the inner dome was originally ventilated with natural light entering through large portholes. The dome has a balustrade running around its perimeter from where visitors can look down to the entrance gallery and grand staircase below. A running band of floral motifs carved in stucco adorns the base of the perimeter.